BERT Model Based Identification and Classification of Web Vulnerabilities Using Deep Learning Approach - M. Kempanna, Pushpa G., Rangaswamy M. G., Manjunatha K. M. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In recent years, researchers have been focused upon machine learning and machine language based models to predict and identify effects of their researches. In this research the vulnerabilities in web, using the machine learning model BERT (Bidirectional Encoder Representations from Transformers) with additional layers have been attempted. The datasets used for the model’s prediction and classification are SQLInjection (SQLI) (namely: attacks and benign) and Cross Site Scripting (XSS) datasets respectively. The developed BERT model predicts the vulnerabilities in the data and classifies them accordingly. The loss is estimated through cross entropy loss technique. The performance of the model is evaluated through metric evaluation method namely binary accuracy. The analyses and findings shows that the developed advanced BERT obtained higher accuracy (SQLI with 98% and XSS with 97% accuracies respectively), than the standard BERT model (SQLI with 87% and XSS with 84% accuracies respectively). The research concludes stating that an increased BERT layers based model performs significantly with higher accuracy in classification than the standard BERT as a transformer model.